Detection of phenylalanine ammonia - lyase activity in different plant parts of anacardium occidentale l. - SIJA.S.L; POTTY.V.P; SANTHOSHLAL.P.S (International Journal of Pharma and Bio Sciences, 2016)
Phenylalanine ammonia-lyase (PAL) performs a major role in the biosynthesis of polyphenolic compounds, which are involved in the defense mechanism in harsh environments related to different stimuli. The present study was carried out to detect the activity of phenylalanine ammonia-lyase in different plant parts of Anacardium occidentale such as flower, young leaves, shoot tip, mature leaves, raw cashew nut shell, shoot, root and cotyledons. The presence of anacardic acid, a phenolic compound in methanolic extract of young leaves of cashew seedling was also detected using high performance thin layer chromatography (HPTLC) method. The results showed that the highest activity rate of PAL was observed in cotyledon (0.611 ± 0.06 U/ml) and least amount in root (0.161 ± 0.02 U/ml).